The new encyclopedia británica in 30 volumes, macropedia VOL.1 Knowledgr in depth / William Benton - Benton, William (Estados Unidos de América: Encyclopedia Británica, Inc)
Aalto, alvar, Abbas I the great, of Persia, a bd al-Malik ibn Marwan, abdelkader, abel, niels Henrik, Abelard, peter, abrasives, abuhanifah, accelerators, particle, acclimatization, acid-base reactions and equilibria, acoustical engineering, an actinide elements and their compounds, Adam Robert.
Ilustración, mapa, tabla
Col. Enc
Keywords: 1. ENCICLOPEDIA 2. ENCYCLOPEDIA BRITANNICA-MACROPEDIA 3. REFERENCIA